Preliminary study assessing the long-term surgical outcomes of TBX6-associated congenital scoliosis (TACS) patients using the propensity score matching method: exploring the clinical implications of genetic discoveries in congenital scoliosis - Guanfeng Lin; Yang Yang; Zefu Chen; Sen Zhao; Yuchen Niu; You Du; Yiwei Zhao; Shengru Wang; Nan Wu; Jianguo Zhang (Orphanet Journal of Rare Diseases)
Abstract Background Compound inheritance of TBX6 accounts for approximately 10% of sporadic congenital scoliosis (CS) cases. Such cases are called TBX6-associated congenital scoliosis (TACS). TACS has been reported to have certain common clinical phenotypes. However, whether the surgical outcomes of TACS patients differ from those of other CS patients remains unclear. Methods We retrospectively searched for patients who were diagnosed with scoliosis. TACS was identified in genetic testing for CS. After propensity score matching, patients with TACS were matched with patients with NTACS according to sex, age, main curvature, classification, deformity location, surgical methods, fusion segment and number of fusions. We evaluated and compared the coronal and sagittal radiographic parameters before surgery, immediately after surgery, and at the final follow-up. Surgical information, including surgical method, fusion segment, blood loss and complications, was also compared and analyzed. Results Twenty-eight TACS patients were propensity score matched with 28 NTACS patients among 473 CS patients. The preoperative matching parameters mentioned in the Methods section were similar between the TACS group and the NTACS group. In the TACS group, the correction rate of the cranial compensatory curve (64.9 ± 18.6% vs. 51.2 ± 24.0%, P = 0.014) and the correction rate of the caudal compensatory curve (77.4 ± 12.5% vs. 65.4 ± 22.7%, P = 0.011) were significantly greater than those in the NTACS group, and the loss rate of correction of the cranial compensatory curve in the TACS group (0.6 ± 19.2% vs. 26.7 ± 50.8, P = 0.002) was significantly lower than that in the NTACS group. The total complication rate (7.2% vs. 14.3%) and incidence of adding-on (0 vs. 7.1%) were lower in the TACS group than in the NTACS group. There were no significant differences between the two groups in terms of blood loss, revision rate, other correction parameters, balance parameters or incidence of complications. Conclusions TACS patients had better surgical outcomes than NTACS patients, which means that genetic diagnosis of the TBX6 gene mutation in CS before surgery can help predict better surgical outcomes. The specific genetic mechanism is not yet clear and may be related to the relatively normal development of paravertebral tissues in TACS patients. Further research is needed. Level of evidence Leve: III.